The impact of import competition from China on firm-level productivity growth in the EU - Klaus S. Friesenbichler; Agnes Kügler; Andreas Reinstaller (Austrian Institute of Economic Research (WIFO), 2021)
We revisit the impact of rising imports from China on within firm labour productivity growth in the EU. The period analysed is 2003 through 2016 and thus covers the recent increase of technology-intensive imports from China. We find that higher fractions of Chinese imports in aggregate imports slow down labour productivity growth of domestic firms in Europe. The adverse effect becomes more pronounced at higher growth rates. Multinationals are able to partly compensate the negative effects of import competition and benefit from Chinese imports at higher productivity growth intensities. The effects are strongest for local firms and firms in low tech industries. No effects were found for firms in high-tech industries.
Keywords: F14; L20; L60; J24; 330; Import Competition; Multinational Firms; Productivity; Manufacturing; EU; China